2023
DOI: 10.51253/pafmj.v73i2.7666
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ultrasound and Computed Tomography in Differentiating Transudate from Exudate in Patients with Pleural Effusion

Abstract: Objective: To compare the diagnostic accuracy of Computed Tomography and Ultrasonography in differentiating trans-dative and exudative pleural effusion. Study Design: Cross-sectional study. Place and Duration of Study: Radiology Department of Pakistan Institute of Medical Sciences, Islamabad Pakistan, from Jul to Oct 2021. Methodology: Patients suffering (n=80) from pleural effusion were involved, and all were assessed with ultrasound and computed Tomography along with diagnostic thoracocente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The diagnostic accuracy of ultrasound and CT in differentiating transudate from exudate in patients with pleural effusion has been a subject of extensive study. Isani et al (2023) (39) highlighted both modalities' diagnostic accuracy, while Soni et al (2022) (40) emphasized the role of ultrasound in measuring pleural fluid echogenicity, contributing to the differentiation between transudative and exudative effusions. Similarly, Ahmed et al (2017) (41) demonstrated ultrasound's utility in diagnosing pleural effusion, further validating its role in clinical assessments.…”
Section: Discussion On Ultrasound's Ability To Differentiate Pleural ...mentioning
confidence: 99%
“…The diagnostic accuracy of ultrasound and CT in differentiating transudate from exudate in patients with pleural effusion has been a subject of extensive study. Isani et al (2023) (39) highlighted both modalities' diagnostic accuracy, while Soni et al (2022) (40) emphasized the role of ultrasound in measuring pleural fluid echogenicity, contributing to the differentiation between transudative and exudative effusions. Similarly, Ahmed et al (2017) (41) demonstrated ultrasound's utility in diagnosing pleural effusion, further validating its role in clinical assessments.…”
Section: Discussion On Ultrasound's Ability To Differentiate Pleural ...mentioning
confidence: 99%